How forage grain ratoon rice improves the grain yield during the ratoon season - Gai, Panpan; Chen, Yuanwei; Sun, Xin; Chen, Hongjing; Yang, Desheng; Ren, Miaofei; Liu, Lei; Wang, Weiqin; Zheng, Hua-bin; Tang, Qiyuan (Frontiers in Plant Science, 2024)
In recent years, with the rapid extension of ratoon rice production in Hunan, one unique ratoon rice-based production systems, forage-grain ratoon rice (FG-RR) have been newly developed. Ratooning rice was a season of rice harvested by utilizing the dormant buds on the stubble left after harvesting the first season of rice to sprout and grow. Therefore, the characteristics of stubble themselves are crucial for the production of ratoon rice. The mowing period and higher stubble height directly affect the characteristics of regenerated stubbles. Based on this, we conducted the following research. In 2021 and 2022, field experiments were conducted in central China to study the effects of different mowing periods and higher stubble height on the regeneration rate and nutrient content of regenerated crops. The treatment includes two mowing periods (10 days after heading in the first season and 30 days after heading in the first season, respectively referred to as T10 and T30) and two stubble heights (10 and 30 cm, respectively referred to as H10 and H30). Compared with T30H30 treatment, T10H10, and T10H30 increased grain yield by 48.1%, 41.7%, 73.1%, and 65.2% in the two year ratoon season, while T30H10 reduced grain yield by 30.9% and 19.5% in the two years, respectively. Early mowing increased the panicles, spikelet panicle, and filled grain rate to varying increase, while higher stubble height increased panicles but decreased spikelet panicle.mowing On the one hand, early mowing and higher stubble height of stubble increased the dry and fresh weight, nonstructural carbohydrate (NSC), organic carbon (C), and nitrogen content of stubble, thereby improving the regeneration rate of ratoon rice. On the other hand, early mowing and higher stubble height retention increased the accumulation of nitrogen in stubble throughout the entire growth period and facilitated the transport of nitrogen to the mature panicles. Therefore, FG-RR appropriate early mowing and higher stubble height are the keys to improving the grain yield and stability of ratoon rice.